Influence of Al2O3nanoparticle doping on depolarization temperature, and electrical and energy harvesting properties of lead-free 0.94(Bi0.5Na0.5)TiO3-0.06BaTiO3ceramics - Pharatree Jaita (2020)
© The Royal Society of Chemistry 2020. In this research article, the effects of Al2O3nanoparticles (0-1.0 mol%) on the phase formation, microstructure, dielectric, ferroelectric, piezoelectric, electric field-induced strain and energy harvesting properties of the 0.94(Bi0.5Na0.5)TiO3-0.06BaTiO3(BNT-6BT) ceramic were investigated. All ceramics have been synthesized by a conventional mixed oxide method. The XRD and Raman spectra showed coexisting rhombohedral and tetragonal phases throughout the entire compositional range. An increase of the grain size,TF-R,Tm,εmaxandδAvalues was noticeable when Al2O3was added. Depolarization temperature (Td), which was determined by the thermally stimulated depolarization current (TSDC), tended to increase with Al2O3content. The good ferroelectric properties (Pr= 32.64 μC cm−2,Ec= 30.59 kV cm−1) and large low-fieldd33(205 pC N−1) values were observed for the 0.1 mol% Al2O3ceramic. The small Al2O3additive improved the electric field-induced strain (Smaxand). The 1.0 mol% Al2O3ceramic had a large piezoelectric voltage coefficient (g33= 32.6 × 10−3Vm N−1) and good dielectric properties (εr,max= 6542,Td= 93 °C,TF-R= 108 °C,Tm= 324 °C andδA= 164 K). The highest off-resonance figure of merit (FoM) for energy harvesting of 6.36 pm2N−1was also observed for the 1.0 mol% Al2O3ceramic, which is suggesting that this ceramic has potential to be one of the promising lead-free piezoelectric candidates for further use in energy harvesting applications.